Investigating the Anti Angiogenic Activity of Carica papaya Leaf Extract - Tayal, Nidhi; Srivastava, Priyansh; Srivastava, Nidhi (Research Perspectives of Microbiology and Biotechnology Vol. 4, 2024)
Cancer is a major cause of death worldwide and angiogenesis is critical in cancer progression. The development of new blood vessels and the nutrition of tumor cells are heavily dependent on angiogenesis. Angiogenesis is the formation of new blood vessels from existing vasculature. In normal physiology, angiogenesis has a role in embryogenesis, the female reproductive cycle, and wound healing and bone formation [1]. There are several “on” and “off” switches that regulate the process. Decreasing or inhibiting angiogenesis can be therapeutic in cancer and other diseases. Thus, angiogenesis is an important process that occurs both during health and disease. This study was conducted to investigate the anti-angiogenic activity of Carica papaya leaf. Fresh green papaya leaves, were randomly collected from Yadav Nursery, Geeta Colony, East Delhi. The anti-angiogenic activity of papaya leaf was evaluated using the docking behaviour of known bioactive compounds of a leaf as ligands with angiogenic receptors VEGFR1 and VEGFR2 along with their putative binding sites using Swiss Dock Web server (In silico) and further based on docking results leaf aqueous extract was used for implantation in the chorioallantoic membrane (CAM) egg yolk angiogenesis model (in vivo). Docking studies and binding free energy calculations revealed that among known bioactive compounds of leaf Ascorbic acid, quercetin, riboflavin and lycopene have maximum free energy as compared to other investigated ligands. Similarly, CAM assay also showed the inhibitory effect of the Carica papaya leaf with respect to their reduction in length, size and junctions of blood capillaries compared to untreated egg yolk. The results showed that Ascorbic Acid, Quercetin, Riboflavin and, Lycopene (leaf compounds) can attenuate angiogenesis in pathological conditions and can be potent in drug discovery as well as medical science. Further studies need to be conducted to determine anti-angiogenic pathways followed by leaf extract or juice. It can be concluded that administration of Carica papaya leaf juice is safe and does induce anti angiogenic process during disease condition like Cancer.